2016
DOI: 10.1172/jci.insight.87157
|View full text |Cite
|
Sign up to set email alerts
|

IL-3 promotes the development of experimental autoimmune encephalitis

Abstract: Little is known about the role of IL-3 in multiple sclerosis (MS) in humans and in experimental autoimmune encephalomyelitis (EAE). Using myelin oligodendrocyte glycoprotein (MOG) peptide-induced EAE, we show that CD4 T cells are the main source of IL-3 and that cerebral IL-3 expression correlates with the influx of T cells into the brain. Blockade of IL-3 with monoclonal antibodies, analysis of IL-3 deficient mice, and adoptive transfer of leukocytes demonstrate that IL-3 plays an important role for developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 55 publications
2
35
1
Order By: Relevance
“…Cx47KO mice showed also higher expression of FasL, which regulates T-cell functions, activates the caspase cascade and is present on glial cells in chronic MS plaques (Dowling et al, 1996;Volpe, Sambucci, Battistini, & Borsellino, 2016). Moreover, IL-2, IL-3, and IL3-beta, involved in MS pathogenesis (Renner et al, 2016;Zandian et al, 2011), showed persistent elevation at 12 dpi in Cx47KO in contrast to WT EAE mice.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cx47KO mice showed also higher expression of FasL, which regulates T-cell functions, activates the caspase cascade and is present on glial cells in chronic MS plaques (Dowling et al, 1996;Volpe, Sambucci, Battistini, & Borsellino, 2016). Moreover, IL-2, IL-3, and IL3-beta, involved in MS pathogenesis (Renner et al, 2016;Zandian et al, 2011), showed persistent elevation at 12 dpi in Cx47KO in contrast to WT EAE mice.…”
Section: Discussionmentioning
confidence: 92%
“…Cx47KO mice showed also higher expression of FasL, which regulates T‐cell functions, activates the caspase cascade and is present on glial cells in chronic MS plaques (Dowling et al, ; Volpe, Sambucci, Battistini, & Borsellino, ). Moreover, IL‐2, IL‐3, and IL3‐beta, involved in MS pathogenesis (Renner et al, ; Zandian et al, ), showed persistent elevation at 12 dpi in Cx47KO in contrast to WT EAE mice. Finally, CCL2 produced by activated astrocytes (Rothhammer & Quintana, ) is significantly upregulated in Cx47KO EAE mice at 7 dpi, before the disruption of BBB/BSCB (Aubé et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on IL-3 knock-out mice showed that IL-3 has minor nonredundant effects on hematopoiesis, but plays a significant role in anti-parasite immunity through its action on mast cells and basophils [46, 53–56]. There is increasing interest in this cytokine given recent reports on the involvement of IL-3 in augmenting features of sepsis, systemic lupus erythematosus or the experimental autoimmune encephalomyelitis model of multiple sclerosis [5759]. …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this event is linked to oligodendrocyte depletion and demyelinating processes [42]. The IL-3 signalling pathway, which is another significant pathway in the NDP group, may be also related to MS. Renner et al [46] exhibited that IL-3 expression in T cells was increased substantially during relapse in RR-MS patients, and an anti-IL-3 monoclonal antibody reduced disease severity in experimental autoimmune encephalomyelitis (EAE). Another over-represented pathway in the NDP group was the TNF-a signalling pathway.…”
Section: Significant Protein Complexes and Ms-related Genes In The Ndmentioning
confidence: 99%